2012
DOI: 10.3892/ol.2012.673
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of MTUS1 mRNA is correlated with poor prognosis in bladder cancer

Abstract: Abstract. Mitochondrial tumor suppressor 1 (MTUS1) is a newly identified candidate tumor suppressor gene. Previous studies have demonstrated that the expression status of MTUS1 is altered in several types of tumors. However, its clinical significance for bladder cancer patients remains undetermined. In this study, we detected the expression of MTUS1 mRNA in bladder tumors and paired normal samples obtained from 5 patients using semi-quantitative reverse transcription-polymerase chain reaction (RT-PCR). A signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Other studies have shown that the MTUS1 gene encoding ATIP3 is significantly downregulated in various types of cancers including from the pancreas (32), ovary (33), head-andneck (34,35), colon (36), and bladder (37). Low MTUS1 levels were also correlated with reduced overall survival of the patients with bladder cancer (37) and oral tongue squamous cell carcinomas (35), highlighting the potential importance of ATIP3 as a new prognostic marker in a variety of solid tumors.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other studies have shown that the MTUS1 gene encoding ATIP3 is significantly downregulated in various types of cancers including from the pancreas (32), ovary (33), head-andneck (34,35), colon (36), and bladder (37). Low MTUS1 levels were also correlated with reduced overall survival of the patients with bladder cancer (37) and oral tongue squamous cell carcinomas (35), highlighting the potential importance of ATIP3 as a new prognostic marker in a variety of solid tumors.…”
Section: Discussionmentioning
confidence: 75%
“…Low MTUS1 levels were also correlated with reduced overall survival of the patients with bladder cancer (37) and oral tongue squamous cell carcinomas (35), highlighting the potential importance of ATIP3 as a new prognostic marker in a variety of solid tumors.…”
Section: Discussionmentioning
confidence: 93%
“…Xiao et al (11) found that MTUS1 expression was correlated with tumor grade, stage, size and number in bladder cancer, and patients with low levels of MTUS1 mRNA expression had a poor prognosis compared with those exhibiting high MTUS1 expression. Our previous study also suggested that downregulation of MTUS1/ATIP was a frequent event in TSCC and premalignant lesions, e.g., leukoplakia.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime another study group also found an association between MTUS1 expression and bladder cancer [30]. …”
Section: Resultsmentioning
confidence: 99%